Forest Steppe-Like Vegetation Near Cherskiy (West Beringia) During the Early Pleistocene Olyorian Period Reconstructed Using Plant Macrofossils - Kienast, Frank; Davydov, Sergei P. (Frontiers in Earth Science, 2021)
The lower Kolyma region is known for rich Early Olyorian large mammal assemblages including plesiomorphic musk ox, reindeer, horse, broad-fronted moose, steppe mammoth and cave bear. Data on the vegetation in zonal habitats from the Olyorian period are, in contrast, scarce. Earlier palynological results from classical Olyorian sites indicated predominant grassland vegetation with scattered larch occurrences but are, due to limited taxonomical resolution, uncertain. Plant macrofossil data were, so far, only available from azonal, aquatic habitats. Here, we describe Olyorian palaeo-vegetation from an exposure near Cherskiy, Nizhnekolymsky District, Sakha Republic, Russia. The macrofossil-based reconstruction of palaeo-vegetation revealed the existence of an open forest steppe comprising a mosaic of sparse larch groves in a dry grassland composed of tundra steppes, degraded meadow steppes and saline meadows. In the larch groves, light demanding shrubs and dwarf shrubs such as shrub birch (Betula cf. fruticosa, B. nana ssp. exilis), raspberry (Rubus idaeus), cowberry (Vaccinium vitis-idaea), and crowberry (Empetrum nigrum) formed the understory. Ruderal pioneer plants point to open ground as result of disturbances, possibly due to the activity of large herbivores. The nitrophytic ruderal species Urtica dioica, in particular, suggests locally increased nutrient supply from animal excretions. Also, the abundant remains of Chenopodium cf. prostratum might be explained by disturbances and nutrient enrichment, but Chenopodium is also characteristic of salt accumulation in the soil owing to high evaporation under arid conditions, which are also indicated by alkali grass (Puccinellia sp.). The presence of trees and shrubs indicates interglacial-like temperature conditions but the dominance of dry grassland species and the occurrence of facultatively halophytic plants (Chenopodium prostratum, Puccinellia sp.) suggests aridity, which is more typical of cold stages. During the early Pleistocene, i.e., prior to the Early-Middle Pleistocene transition (EMPT) culminating around 900 ka ago, the duration of climate cycles was shorter and the amplitude of climate fluctuations was smaller. Ice-rich permafrost formed only after the EMPT during increasingly extreme cold stages, and, during warm stages, its thawing resulted in paludification of the active layer. Prior to the EMPT, the climate in West Beringia was constantly relatively dry, more or less moderate and more stable than thereafter. In contrast to modern tundra and northern taiga in the study region, dry habitats apparently prevailed during the time of deposition of the plant macro-remains.